Statistical Analysis of Foreign Investment Using Neutrosophic Interval Based Approach - Jamil Afzal; Naim Mathlouthi; Mohamed Saer Rahal; Chen Yongmei; Aftab Haider; Muhammad Adeel Afzal (Neutrosophic Sets and Systems)
Pakistan, a nation at the crossroads of South Asia, has been actively striving to attract foreign investment to boost its economic growth and development. As a country rich in natural resources, with a young and vibrant workforce, and a strategic geographic location, Pakistan offers significant opportunities for foreign investors seeking to explore new markets and tap into its potential. The foreign investment policies in Pakistan have undergone substantial reforms over the years to create a more investor-friendly environment. These policies are designed to facilitate and incentivize foreign direct investment while ensuring the protection of investors' rights and contributing to the overall economic progress of the country. The government of Pakistan, recognizing the critical role of foreign investment in driving economic transformation, has implemented various initiatives and measures to attract investors from around the world. The purpose of this study was to investigate the use of Neutrosophic Analysis during Statistical Analysis of Foreign Investment using Imprecise Information, and this approach provides remarkable results. The neutrosophic approach has provided a comprehensive understanding of the various perspectives and uncertainties involved in foreign investment strategies. This study's results demonstrated that this Interval-Based Approach may be used for better understanding instead of the classical approach.